1993
DOI: 10.1097/00001888-199307000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for estimating the real cost of an objective structured clinical examination

Abstract: A major impediment to the use of the objective structured clinical examination (OSCE) is that it is a labor-intensive and costly form of assessment. The cost of an OSCE is highly dependent on the particular model used, the extent to which hidden costs are reported, and the purpose of the examination. The authors detail hypothetical costs of running a four-hour OSCE for 120 medical students at one medical school. Costs are reported for four phases of this process: development, production, administration, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 0 publications
1
41
0
4
Order By: Relevance
“…There were significant costs associated with the OSCE component of the PRE. These were comparable to those reported in the literature 25 and deemed justifiable for the outcomes achieved.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There were significant costs associated with the OSCE component of the PRE. These were comparable to those reported in the literature 25 and deemed justifiable for the outcomes achieved.…”
Section: Discussionsupporting
confidence: 89%
“…The OSCE was identified as being one of the most resource intensive components of the PRE, and the costs estimated in accordance with Reznick and colleagues "Guidelines for Estimating the Real Cost of an Objective Structured Clinical Examination". 25 The costs were estimated in the four phases of implementation of an OSCE namely: examination development, examination production, examination administration and post-examination analysis.…”
Section: A J P Ementioning
confidence: 99%
“…23 Other studies, looking just at per-student costs, found a range from a low of $54 to a high of $496 per student. 6,7,24 The discrepancies in cost were related to differences in pay to the standardized patients, honoraria for the faculty, number of stations and examinees, and total time of the examination.…”
Section: Potential Pitfalls Of the Oscementioning
confidence: 99%
“…De kosten van simulatietoetsen zijn hoog. 26 Toetsing van echte consulten in de klinische praktijk heeft een aantal financiële voordelen. Er zijn geen kosten voor het schrijven en valideren van simulatiecasus, voor reiskosten en training van simulatiepatiënten, huur van ruimtes in een skillslab en de inrichting ervan (instrumentarium en verbruiksgoederen).…”
Section: Belangrijke Psychometrische Aspecten Van 'In Vivo' Toetsingunclassified